Delay Analysis of Proposed DMN Algorithm in VANET - Sharma, Vishnu; Goyal, Ankur (International Journal of Computer Sciences and Engineering, 2019)
Wireless networks are the technology changer that has changed the modern communication system. In the field of intelligent transport system, wireless network play an important role in the form of Vehicular Adhoc Network (VANET). VANET is a special type of adhoc wireless network which is characterised with fast moving vehicle node, high vehicle speed, and moving along the road. But the VANETs have the security issues. The different malicious nodes present in the coverage decrease the efficiency of the network. Researchers have performed lot of work to secure the VANET. In this work, a new algorithm is proposed for the detection of malicious nodes in VANET. The proposed algorithm is designed and implemented. The results show that there is improvement in the VANET.